A thanatophoric dysplasia type i case with a fgfr3 p.r248c mutation and survival ibeyond the neonatal period - (:unkn) unknown (Editions Medecine et Hygiene, 2016)
A thanatophoric dysplasia type / case with a FGFR3 p.R248C mutation and survival beyond the neonatal period: Thanatophoric dysplasia, is a severe congenital anomaly which mostly causes stillbirth or death of the affected baby within hours due to respiratory insufficiency. The diagnosis ofTD is typically suspected on ultrasound during the second trimester of pregnancy, when severe shortening of the long bones, frontal bossing, flattened vertebrae, and short ribs that result in a narrow thorax and bell-shaped abdomen, can be seen. Here, we present a case with prenatal ultrasonographic findings suggestive of TD, and highlight the patient's postnatal dysmorphic features and typical radiographic findings. The definitive diagnosis of TD type 1 (TD1) was made postnatally, when molecular genetic analysis revealed the previously described p.R248C mutation in FGFR3. This case is reported due to its relative long life span and the definitive molecular diagnosis that could be made during hospitalization.
Keywords: FGFR3; Hanatophoric dysplasia; Lifespan; Skeletal dysplasia